Mega events and the restoration of urban land - Wilson, Mark (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
One of the most productive uses of ephemeral events like the Olympics, Expos and FIFA World Cup is to use them to produce a better city. These events often require considerable changes in land use and investments in infrastructure that need to serve not only the event but also future needs as well. One valuable urban application is to reuse polluted or aging industrial land and turn it into a city asset. Brownfield development as part of mega events can lead to reclamation of beaches and waterfronts, and the use of industrial land for commercial and residential use. Examples drawn from recent mega events illustrate how careful planning can leave an event legacy of improved land use and quality of life.